1993
DOI: 10.1056/nejm199308123290707
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Care for Women -- Does the Sex of the Physician Matter?

Abstract: Women are more likely to undergo screening with Pap smears and mammograms if they see female rather than male physicians, particularly if the physician is an internist or family practitioner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
247
9
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 444 publications
(281 citation statements)
references
References 11 publications
23
247
9
2
Order By: Relevance
“…Male physicians in this study were also less likely to follow cervical cancer screening guidelines, consistent the physician gender bias seen in published research from the general population [23,24].…”
Section: Breast and Cervical Cancer Screeningsupporting
confidence: 88%
“…Male physicians in this study were also less likely to follow cervical cancer screening guidelines, consistent the physician gender bias seen in published research from the general population [23,24].…”
Section: Breast and Cervical Cancer Screeningsupporting
confidence: 88%
“…Our study also substantiated findings demonstrating disparities in the breast care process associated with clinician gender [11][12][13] . While the benefits of self breast exams and clinical breast exams are controversial 14 , Lurie and colleagues showed that female physicians are more likely to talk with patients about breast cancer prevention, to believe in the effectiveness of mammography, and to feel comfortable performing clinical breast examinations 13 .…”
Section: Discussionsupporting
confidence: 87%
“…However, an analysis examining language concordance with Chinese American providers and mammography screening showed that language concordance with Chinese female providers was positively associated with screening [23]. Additional analysis from this study supports the key role of the provider's gender: having Chinese and non-Chinese female physicians were associated with higher rates of breast and cervical cancer screening in the US and Vancouver [48][49][50][51], while women with Chinese male physicians had the lowest screening rates. Of note, a majority of Chinese women in Vancouver, and significantly fewer in Seattle, reported that they had a Chinese male physician.…”
Section: Discussionmentioning
confidence: 58%